The vinyl bromide optically pumped far infrared laser: New large offset emissions - Moretti, A.; Bertolini, A.; Carelli, G.; Nannizzi, M.; Moraes, João Carlos Silos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
We present the results of a study on vinyl bromide for the search for new far infrared (FIR) laser lines. As the pump source, we use a CW waveguide CO2 laser with a tunability of 290 MHz around each line in order to pump large offset vibrational transitions. As a consequence, we obtained 28 new FIR laser emissions; 24 of them have wavelengths greater than 500 mum and are, therefore, suitable to be used in high-field EPR spectroscopy, For each of the new lines, we give the wavelength, the offset of the pumping transition with respect to the center Frequency of the CO2 emission, the polarization relative to that of the pumping laser line, the operating pressure, and the relative intensity. We also present a catalog including data of all of the FIR laser lines observed from this molecule up to now.
Keywords: gas lasers; infrared; submillimeter-wave lasers; vinyl bromide